Ruggedness of 1200 V SiC MPS diodes. Issue 9 (August 2015) - Fichtner, S.; Frankeser, S.; Lutz, J.; Rupp, R.; Basler, T.; Gerlach, R.
Abstract: SiC merged-pin-Schottky (MPS) diodes possess fast switching ability combined with low losses. Compared to conventional Schottky diodes they also provide a high surge current capability making them rugged against surge current pulses of more than seventeen times the rated current for a 10 ms half-sine pulse. In this paper further aspects of device ruggedness are presented such as the surge current capability of two diodes in parallel and the turn-off behavior at application condition and at overcurrent. It was found that the turn-off characteristics are almost independent from the applied voltage. Further, the diode could withstand turn-off from fifteen times the rated current. Highlights: The surge current ruggedness of 1200 V MPS diodes from Infineon does not degrade in parallel arrangement. The current waveform during turn-off at nominal current is almost independent of the applied voltage. The diode withstands turn-off from fifteen times the rated current with high current and voltage slopes.